Aquifer-Peatland Hydrological Connectivity and Controlling Factors in Boreal Peatlands - Lambert, C.; Larocque, M.; Gagné, S.; Garneau, M. (Frontiers in Earth Science, 2022)
The conditions in which groundwater inflow occurs in oligotrophic boreal peatlands of eastern Canada and its contribution to peatland water balance are still poorly understood. The objectives of this research were to quantify the hydrological connectivity between a surficial aquifer and a peatland, and to identify the controlling factors in boreal peatlands of north-central Quebec (Canada). The peatlands were instrumented with piezometers and groundwater levels were monitored during two growing seasons. Hydraulic conductivities were measured on peat cores and in situ, groundwater inflows and outflows were calculated using the Darcy equation. The peatland water budgets were simulated for the two peatlands with a steady-state groundwater flow model to verify flow hypotheses, to quantify unmeasured flows and to explore recharge scenarios leading to changes in connectivity. The two peatlands have contrasted water budgets, with recharge representing the largest inflow (78%) and subsurface runoff representing the largest outflow at the peatland with the smallest catchment area (85%; Misask). The peatland with the largest catchment area (Cheinu) is also located downgradient within the regional watershed. Its inflows are dominated by groundwater (56%) and its outflows are mostly towards subsurface runoff (74%). The two peatlands are in conditions of precipitation excess and a recharge reduction would not affect their peatland heads markedly (< 10 cm). However, recharge changes could induce larger modifications in groundwater inflows and outflows for the peatland with a larger catchment area. The dominating peatland hydrological functions are thus contrasted at the two sites, and it is hypothesized that the water table depths thresholds triggering changes between storage, transmission and runoff functions are also different. Although further studies remain to be done to understand how hydrological conditions change through time, and ultimately what are the long-term impacts of a changing climate on hydrology, vegetation and carbon accumulation, this work shows that understanding peatland hydrology requires to consider hydrological conditions beyond the peatland limits.